Motivational pathways towards academic achievement in physics & chemistry: a comparison between students who opt out and those who persist. Issue 3 (19th June 2019) - Ardura, Diego; Pérez-Bitrián, Alberto
Abstract : The main goal of the present investigation was to analyze the effect of motivation towards physics & chemistry on achievement in secondary school students. We focused our interest on the comparison between students who chose the subject when becoming optional in the Spanish educational system and those who opted out. Our analyses uncovered the existence of three different motivational profiles towards achievement in physics & chemistry, depending on the students' decisions to persist or to leave. Regardless of their choice, self-efficacy played a key role, not only as a direct predictor of academic achievement but also as a facilitator of the indirect effects of other motivational variables on academic performance. However, our models showed that, for students who opt out physics and chemistry, grade motivation and self-determination are more important predictors of performance than for those who choose the subject. Gender effects and educational implications are also addressed.